Flipped Classroom and Aronson´s Puzzle: a Combined Evaluation in the Master´s Degree in Preuniversitary Teaching - Lázaro-Carrascosa, Carlos; Hernán-Losada, Isidoro; Palacios-Alonso, Daniel; Velázquez-Iturbide, Ángel (Education in the knowledge society, 2021)
This article presents a double evaluation carried out in the subject Complements for disciplinary training II: Computing, corresponding to the Master's degree teacher training in secondary education, baccalaureate, vocational training and languages taught by the Universidad Rey Juan Carlos. The students of the subject had to learn how to prepare simple web pages, using HTML, CSS and JavaScript programming languages. To this end, the flipped classroom technique was used to present the necessary contents, combined with the adaptation of Aronson's cooperative learning puzzle technique, used to carry out a group practice that reflected the knowledge acquired. It is worth mentioning, as a complement to the two techniques used, the use of an adapted assessment rubric, which was provided to the students at the beginning of the teaching block. The evaluation was carried out during two consecutive academic years, 2018/2019 and 2019/2020. There were important differences between the two studies: in the first study, the students' previous self-assigned level was much higher (2.8 points as opposed to 1.4 points on a scale of 1 to 5). The other difference, even more relevant, was that in the second year all teaching was done at home, in a non-attendance format, on a mandatory basis, due to the period of confinement decreed by the state of alarm at that moment, because of the pandemic caused by the SARS-CoV-2 virus, popularly known as coronavirus. At the end of the experience, the students expressed their satisfaction with the learning acquired and with the tasks performed, in both cases. The techniques used were well-appreciated, in the first year more than in the second, and especially flipped classroom. The scores obtained were, in addition, always very relevant.